Penentuan Audit Opini Kelangsungan Hidup Pada Perusahaan Sektor Transportasi Yang Terdaftar Pada Bursa Efek Indonesia - Candra, Heryanto; Ramadhan, Yanuar (E-Jurnal Akuntansi; Vol 32 No 6 (2022), 2022)
The research is based on the phenomenon which states that there are 35 problematic companies that receive going concern audits on the Indonesia Stock Exchange. This study aims to examine and analyze the effect of firm growth, firm size, and leverage on going-concern audit opinion. Aviation sector companies listed on the IDX for the 2016-2020 period are sampled in this study. The method of data analysis in this study uses logistic regression because there is a dummy variable as an indicator of the dependent variable. The results of the analysis test showed that the variables of company growth and company size had no effect on going-concern audit opinion. While the leverage variable has an effect on going concern audit opinion. Keywords: Firm Growth; Firm Size; Leverage; Opini Audit Going Concern.